2022
DOI: 10.1007/s10643-022-01384-5
|View full text |Cite
|
Sign up to set email alerts
|

Distance Learning in Early Childhood During the COVID-19 Crisis: Family and Educators’ Experiences

Abstract: The COVID-19 crisis presented teachers and families with the challenge of educating young children online. This study explored the experiences with virtual education of 51 parents and 53 teachers of young children. The results have shown that families and educators were aligned in their goals for early childhood education. Nevertheless, teachers rated the online environment as significantly more effective at achieving these goals than parents did. Similarly, families rated online activities as significantly le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In the discussion of our findings, it is evident that the majority of educators demonstrated a favorable attitude toward distance learning, a trend also documented in the research by Plotka and Guirguis (2023). In the study by Bubb and Jones (2020), some preschool educators reported a reduction in their workload, allowing them to dedicate more attention to students.…”
Section: Discussionsupporting
confidence: 76%
“…In the discussion of our findings, it is evident that the majority of educators demonstrated a favorable attitude toward distance learning, a trend also documented in the research by Plotka and Guirguis (2023). In the study by Bubb and Jones (2020), some preschool educators reported a reduction in their workload, allowing them to dedicate more attention to students.…”
Section: Discussionsupporting
confidence: 76%
“…Teaching remotely presented a challenge to all K-12 educators, as well as faculty at the undergraduate and graduate level (e.g. Kim, 2020;Plotka & Guirguis, 2020). Specifically, remote teaching in the early childhood grades created a unique set of challenges due to the active nature of young children's learning; these challenges directly impacted the engagement of young children in meaningful learning experiences.…”
Section: Research Articlementioning
confidence: 99%
“…During the shutdown, teachers also experienced challenges connecting with caregivers, due to the loss of face-to-face contact, particularly at drop-off and pick-up times or during planned family engagement events (Ford et al, 2021 ; Levickis et al, 2022 ). Teachers compensated in a variety of ways: by instituting regular phone check-ins; sharing via text, Facebook Messenger, or similar two-way text-based app use; or sending email updates to the whole class or to individual caregivers (Ford et al, 2021 ; Plotka & Guirguis, 2022 ; Silver & Coba-Rodriguez, 2022 ). Eventually, some programs began to use interactive video-based platforms such as Zoom or WhatsApp for family conversations or events (Levickis et al, 2022 ), while others also adopted platforms designed for use in education (Levickis et al, 2022 ; Silver & Coba-Rodriguez, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the pandemic progressed, many programs moved to online or hybrid instruction, which presented new challenges for teachers and parents. Surveys of educators and families revealed that both groups understood that distance learning for preschool children required caregiver involvement (Ford et al, 2021 ; Plotka & Guirguis, 2022 ; Stites et al, 2021 )—involvement that both groups understood to be difficult for parents, especially when they had to work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation